Inversion of frequency in key schemes for airborne power systems - Пьяных, Б. Е. (Proceedings of National Aviation University (archive), 2000)
The process of formation of curves of electric voltage and current are considered for the converter devices of airborne power supply systems. It is shown that discrete principle allows to provide high quality of electric energy on the output of such devices at maximum energetic losses